1984
DOI: 10.1111/j.1365-2044.1984.tb07363.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure after phenoperidine

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In this respect there was no difference between the effects of phenoperidine alone or phenoperidine combined with pancuronium. These results are in agreement with the observations of Grummitt and Goat (1984), who suggested that phenoperidine may actively increase cerebral blood flow (CBF), and therefore ICP, by inducing cerebral vasodilatation.…”
Section: Discussionsupporting
confidence: 93%
“…In this respect there was no difference between the effects of phenoperidine alone or phenoperidine combined with pancuronium. These results are in agreement with the observations of Grummitt and Goat (1984), who suggested that phenoperidine may actively increase cerebral blood flow (CBF), and therefore ICP, by inducing cerebral vasodilatation.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is no objective evidence that it has any advantage over other drugs. It may increase intracranial pressure [31] and its cardiovascular effects are rather more significant than those of other opioids. Phenoperidine causes peripheral vasodilatation, and arterial pressure decreases by up to 20% in non-ICU patients [51].…”
Section: Phenoperidinementioning
confidence: 99%